INOVASI PEMANFAATAN IKAN LELE (CLARIAS BATRACUS) MENJADI PRODUK OLAHAN LELE (ABON, BROWNIS, DAN KUE KERING) DI DESA CANDIPARI SIDOARJO: INOVASI PEMANFAATAN IKAN LELE MENJADI PRODUK OLAHAN LELE - Ani Masrufah; Khilyatul Afkar; Laily Noer Hamidah; Ardhana Rahmayanti; Elsa Rosyidah; Atik Widiyanti; Listin Fitrianah; Lily Oktavia (Universitas Nahdlatul Ulama Sidoarjo, 2021)
Catfish is one type of freshwater fish that is widely cultivated in Indonesia. Candipari Village isone of the villages, where the people cultivate catfish. So far, catfish is only used as a daily sidedish, but community service activities in Candipari Village, especially catfish farmers, aretaught to process catfish into new healthy preparations. The method used in this activity isdemonstration. The purpose of this activity is to improve community skills in processing catfishinto various processed foods such as shredded, brownies, and pastries. The result of this activityis that the community is skilled at making shredded, brownies, and pastries from catfish.